2012
DOI: 10.1029/2011jd016967
|View full text |Cite
|
Sign up to set email alerts
|

Sun‐Moon gravitation‐induced wave characteristics and climate variation

Abstract: [1] Understanding periods associated with climate variations has been challenging and has attracted scientific study. In the work presented here, we establish a theoretical dynamical model driven by Sun-Moon gravitation (SMG) and present basic SMG wave characteristics and SMG-induced nonlinear motions for geophysical fluids. As compared to observations, waves and motions demonstrate climate variations associated with abundant structures and climatic rhythms, including the 30-60 day oscillation, seasonality, El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 84 publications
1
44
0
Order By: Relevance
“…Our results indicate that the Mediterranean climate during the MSC peak was characterized by climatic oscillations similar to those observed during the past few centuries, likely regulated by astronomical cycles related to the Moon and to the natural oscillations of the Sun and the heliosphere (Scafetta 2010;2012a, 2012b, 2012c, 2012d, Wang et al 2012. Evaporite deposition was caused by precipitation at the pycnocline interface induced by intense evaporation during the driest season and hampered by water-mass dilution related to precipitation and fluvial runoff increase during the wet season (Fig.…”
Section: Main Implications For the Messinian Salinity Crisismentioning
confidence: 75%
See 2 more Smart Citations
“…Our results indicate that the Mediterranean climate during the MSC peak was characterized by climatic oscillations similar to those observed during the past few centuries, likely regulated by astronomical cycles related to the Moon and to the natural oscillations of the Sun and the heliosphere (Scafetta 2010;2012a, 2012b, 2012c, 2012d, Wang et al 2012. Evaporite deposition was caused by precipitation at the pycnocline interface induced by intense evaporation during the driest season and hampered by water-mass dilution related to precipitation and fluvial runoff increase during the wet season (Fig.…”
Section: Main Implications For the Messinian Salinity Crisismentioning
confidence: 75%
“…The periodicities recognized in our study resemble the ones associated to the QuasiBiennial Oscillation, the El Niñ o Southern Oscillation, the sunspotnumber solar cycle and, interestingly, the 9 year periodicity related to a lunisolar tidal cycle. All of these represent the main climate forcing mechanisms that regulated temperature and precipitation in the Mediterranean in the past 500 years (Camuffo et al 2010;Scafetta 2010Scafetta , 2012aWang et al 2012). We suggest that during the MSC, at least during the insolation minima when evaporites precipitated, the Mediterranean did not have a constant hydrological budget but was rather characterized by a highly dynamic climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional Soli-lunar harmonics are present too and interfere with each other generating the El Niño-Southern Oscillation-like inter-annual variation (cf. Wang et al, 2012).…”
mentioning
confidence: 99%
“…Superimposed on these long-term trends of minima and maxima are short-term fluctuations caused by the Schwabe cycle [8], [9]. Furthermore, other studies suggest that the climate and atmospheric oscillations, such as the Pacific Decadal Oscillation (PDO), the Atlantic Multidecadal Oscillation (AMO) and El Niño Southern Oscillation (ENSO), are synchronized to the natural oscillations of the Solar System, which are driven by the movements of the planets around the Sun and lunar gravitational tides [7], [10]- [12]. In addition, Chambers et al [13] identified multi-decadal oscillations of about 60 years in most of the ocean tide gauges examined, which are believed to be related to wind forcing and current variations [14].…”
Section: Introductionmentioning
confidence: 99%